Automated Buildup of Biomimetic Films in Cell Culture Microplates for High‐Throughput Screening of Cellular Behaviors. Issue 27 (22nd May 2018) - Machillot, Paul; Quintal, Catarina; Dalonneau, Fabien; Hermant, Loic; Monnot, Pauline; Matthews, Kelsey; Fitzpatrick, Vincent; Liu, Jie; Pignot‐Paintrand, Isabelle; Picart, Catherine
Abstract: An automatic method is established for layer‐by‐layer (LbL) assembly of biomimetic coatings in cell culture microplates using a commercial liquid‐handling robot. Highly homogeneous thin films are formed at the bottom of each microwell. The LbL film‐coated microplates are compatible with common cellular assays, using microplate readers and automated microscopes. Cellular adhesion is screened on crosslinked and peptide‐functionalized LbL films and stem cell differentiation in response to increasing doses of bone morphogenetic proteins (2, 4, 7, 9). This method paves the way for future applications of LbL films in cell‐based assays for regenerative medicine and high‐throughput drug screening. Abstract : Automated liquid handling of polyelectrolytes in multiple well plates enables highly homogeneous layer‐by‐layer films to be deposited at the bottom of 96‐well plates. Biomimetic films are interesting for cell‐based assays in regenerative medicine. As a proof of concept, cell adhesion and spreading are studied on adhesive peptide‐presenting films and cell differentiation in response to different osteoinductive proteins from the bone morphogenetic protein family.